AUDIO CONTROL CIRCUIT, HOST DEVICE AND ASSOCIATED CONTROL METHOD - Liu, Chao-Wei; Liu, Cheng-Kai; Chen, Ko-Wei (2022)
The present invention provides an audio control circuit (120), wherein the audio control circuit (120) includes a USB interface circuit (124), a specific interface circuit (126) and a processing circuit (122). In the operation of the audio control circuit, the processing circuit (122) receives a plurality of parameters from a host device (110) through the specific interface circuit (126); and during an enumeration between the audio control circuit and the host device (110), the processing circuit (122) uses the plurality of parameters to perform the enumeration.